An IFPI Temperature Sensor Fabricated in an Unstriped Optical Fiber with Self-Strain-Compensation Function. (10th November 2016) - Song, Yang; Hua, Liwei; Lei, Jincheng; Zhang, Qi; Liu, Jie; Ye, Lingyun; Xiao, Hai
Abstract : This paper describes an intrinsic Fabry-Perot interferometer (IFPI) temperature sensor with self-strain-compensation function. The sensor was fabricated on a buffer-intact optical fiber using a femtosecond (fs) laser system. The use of fs laser allows the sensor to be fabricated in an optical fiber without the necessity of removing the polymer buffer coating, thus not compromising its mechanical property. The sensor is composed of two cascaded IFPIs in different cavity length of 100  μ m and 500  μ m, respectively. The shorter IFPI serves as the temperature sensor, while the second IFPI serves as a compensation sensor, which is used to decouple the strain from the raw signal collected by the shorter FPI. The reflection spectrum of sensor, containing both sensory information and compensation information, is collected in wavelength domain and demultiplexed in the Fourier domain of reflection spectrum. An algorithm was developed and successfully implemented to compensate the strain influence on the proposed temperature sensor. The results showed that the proposed sensor structure holds a constant temperature sensitivity of 11.33 pm/°C when strained differently.